Estimation of fuel particle balance in steady state operation with hydrogen barrier model. (May 2019) - Hanada, K.; Yoshida, N.; Takagi, I.; Hirata, T.; Hatayama, A.; Okamoto, K.; Oya, Y.; Shikama, T.; Wang, Z.; Long, H.; Huang, C.; Oya, M.; et al.
Highlights: A simple calculation with rate equations and wall models to study fuel particle balance was developed. The simple calculation with rate equations and the H barrier model was most accurate in comparison with experimental results. The calculation indicates unconsidered fuel supply is necessary to sustain the discharge, although the source of this is still unknown. Abstract: This research investigated fuel particle balance during long duration discharge in an all-metal plasma facing wall (PFW) through intensive QUEST execution. A simple wall model including the plasma-induced deposition layer that creates hydrogen (H) barriers, called the H barrier model, was established. A simple calculation, based on a combination of H state rate equations and the H barrier model, was applied to real plasma in the early phase of its longest discharge. The model accurately reconstructed the evolutions of electron density and wall-stored H over time, proper values are chosen for the parameters that are difficult to determine experimentally. Comparative calculations that used the H barrier and a fully reflective models, predicted significant impacts of wall models on the plasma density time response and value of electron density, indicating that a proper wall model should be developed for all-metal PFW devices.